2017
DOI: 10.1186/s13287-017-0503-8
|View full text |Cite
|
Sign up to set email alerts
|

Repeated intra-articular injection of allogeneic mesenchymal stem cells causes an adverse response compared to autologous cells in the equine model

Abstract: BackgroundIntra-articular injection of mesenchymal stem cells (MSCs) is efficacious in osteoarthritis therapy. A direct comparison of the response of the synovial joint to intra-articular injection of autologous versus allogeneic MSCs has not been performed. The objective of this study was to assess the clinical response to repeated intra-articular injection of allogeneic versus autologous MSCs prepared in a way to minimize xeno-contaminants in a large animal model.MethodsIntra-articular injections of bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
156
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(163 citation statements)
references
References 57 publications
4
156
0
3
Order By: Relevance
“…Our study did not identify any significant differences in the clinical, cytological or biomarker response of the metacarpophalangeal joint to intra‐articular injection of allogeneic vs. autologous BMDMSCs. Previous studies which administered treatments (allogeneic vs. autologous MSCs) into different joints or different cohorts of horses are in agreement with these results . In addition to cell counts and differential cytology results which have been previously reported, our study investigates a synovial inflammatory mediator (PGE 2 ) and an acute phase protein (CRP).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our study did not identify any significant differences in the clinical, cytological or biomarker response of the metacarpophalangeal joint to intra‐articular injection of allogeneic vs. autologous BMDMSCs. Previous studies which administered treatments (allogeneic vs. autologous MSCs) into different joints or different cohorts of horses are in agreement with these results . In addition to cell counts and differential cytology results which have been previously reported, our study investigates a synovial inflammatory mediator (PGE 2 ) and an acute phase protein (CRP).…”
Section: Discussionsupporting
confidence: 87%
“…Likewise, multiple injections of allogeneic or autologous mesenchymal stem cells may result in a different cytological or clinical response as found by Joswig et al . .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that equine BM‐MSCs maintain constitutive surface expression of major histocompatibility complex (MHC) class I with variable surface expression of MHC class II and that equine allogeneic donor BM‐MSCs that are MHC‐mismatched to the recipient can elicit recipient T‐cell response in vitro . Additionally, allogeneic donor equine MSCs are capable of producing antibody responses in vivo in MHC‐mismatched recipients and repeated intra‐articular equine allogeneic MSC injections have been shown to cause an adverse response and more pain when compared to autologous MSC injections . Nevertheless, allogeneic therapy has been used clinically in a variety of conditions in equine medicine with no long‐term adverse effects noted .…”
Section: Discussionmentioning
confidence: 99%
“…Another report comparing autologous and allogenic BM‐MSC joint injections showed no significant difference after a single injection . However, after a second injection, joints receiving allogenic cells demonstrated significantly greater TNCCs than those injected with autologous cells.…”
Section: Discussionmentioning
confidence: 97%
“…However, after a second injection, joints receiving allogenic cells demonstrated significantly greater TNCCs than those injected with autologous cells. It is important to note, that BM‐MSCs from one donor horse assigned to the allogenic group were also found to be positive for MHC II .…”
Section: Discussionmentioning
confidence: 99%